2017
DOI: 10.1071/rd15409
|View full text |Cite
|
Sign up to set email alerts
|

Local effect of lysophosphatidic acid on prostaglandin production in the bovine oviduct

Abstract: The mammalian oviduct plays an important role in the fertilisation and transport of gametes and embryo. Prostaglandins (PGs) are local mediators of oviductal functions and are involved in fertilisation and the transport of gametes and embryo. Lysophosphatidic acid (LPA), a kind of phospholipid, is involved in various physiological actions. We hypothesised that LPA regulates PG production in the bovine oviduct. To test this hypothesis, we examined the mRNA expression of LPA receptors (LPAR1-6) and LPA-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A significant immunoreaction of ATX, together with co-existing PLA 2 enzymes in oviductal epithelia, suggests rat oviductal cavity as a site of LPA production and/or secretion. The existence of LPA producing machinery is partly supported by very recent and detailed studies with a bovine model by Woclawek-Potocka and Yamamoto’s groups [ 29 , 37 ]. They demonstrated expression of mRNAs for ATX, group IVA PLA 2 , and PLA 1 α in epithelial and stromal cells and LPA content in oviductal tissues.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A significant immunoreaction of ATX, together with co-existing PLA 2 enzymes in oviductal epithelia, suggests rat oviductal cavity as a site of LPA production and/or secretion. The existence of LPA producing machinery is partly supported by very recent and detailed studies with a bovine model by Woclawek-Potocka and Yamamoto’s groups [ 29 , 37 ]. They demonstrated expression of mRNAs for ATX, group IVA PLA 2 , and PLA 1 α in epithelial and stromal cells and LPA content in oviductal tissues.…”
Section: Discussionmentioning
confidence: 92%
“…However, ATX/LPA system in post-ovulation processes such as the dynamics of released COCs and fertilizing and dividing potential within the oviduct remains to be clarified. Very recent studies with a bovine model demonstrated mRNA expression of synthetic enzymes (ATX, Group IVA PLA 2 , and PLA 1 α) and signaling receptors (all LPA receptors except for LPA 5 ) in the oviduct [ 29 , 37 ]. Given these findings, we here focus on 1) expression of enzyme and receptor proteins in ovulated COCs and the oviduct and 2) possible in vivo functional role(s) of ATX/LPA system in COCs around fertilization in a rat model.…”
mentioning
confidence: 99%
“…However, it reaches the highest level of expression in the brain [14]. Abovine study also revealed its presence in oviductal epithelial cells and the role of LPA in fertilization, as well as in gamete and embryo transport through an influence on prostaglandin production [15].…”
Section: Figurementioning
confidence: 89%
“…Recent studies revealed the crucial role of PA in embryonic development of animals. Locally produced lysophosphatidic acid (LPA, an intermediate of PA pathway), stimulates PG production and regulates the oviductal functions, and further participates in fertilization and transport of gametes and embryo [ 18 ]. In addition, phospholipase D1 (PLD1)-produced PA activates mTORC1 kinase activity, which in turn promotes decidualization and the successful implantation of embryo [ 19 ].…”
Section: Introductionmentioning
confidence: 99%